The anti-aging effects of Renshen Guben on thyrotoxicosis mice: Improving immunosenescence, hypoproteinemia, lipotoxicity, and intestinal flora - Feng, Qin; Li, Guangyan; Xia, Wenkai; Dai, Guoxin; Zhou, Jidong; Xu, Yan; Liu, Deshan; Zhang, Guimin (Frontiers in Immunology, 2022)
With the rapid aging of the population, the control of age-related disease susceptibility and prognosis faces greater challenges. There is an urgent need for a strategy to maintain the vitality of elderly people. In this study, the effect of Renshen Guben (RSGB) oral liquid was investigated on an accelerated aging mice model of thyrotoxicosis by conventional detection methods combined with multiomics technology. The results showed that RSGB increased the number of neutrophils and lymphocytes, enhanced the function of lymphocytes, and increased the levels of complement and antimicrobial peptides, which indicated that RSGB improved the immunity of thyrotoxicosis mice at the cellular and molecular levels. RSGB corrected malnutrition in thyrotoxicosis mice by improving anemia, hypoalbuminemia, ion transporters, and vitamin-binding proteins. RSGB significantly reduced the lipotoxicity by reducing the level of fatty acids, triglyceride, sphingolipids, and glucocorticoids, thus increasing the level of docosapentaenoic acid (DPA) and bile acids, which contributed to improve immunosenescence. The intestinal defense ability of thyrotoxicosis mice was enhanced with the increase of bile acids and lactic acid bacteria by the RSGB treatment. The plant metabolomics analysis showed that there were various active components in RSGB oral liquid and medicated serum, including terpenoids, phenolic acids, flavonoids, tannin, alkaloids, organic acids, phenolamines, amino acids, and others. They have antioxidant, immune regulation, and anti-aging effects, which was the material basis of RSGB. Totally, RSGB protected the thyrotoxicosis mice against aging by improving immunosenescence, hypoproteinemia, lipotoxicity, and the intestinal flora. It will be beneficial for improving the disease susceptibility and prognosis of the elderly.